Prevalence and distribution of ringed sideroblasts in primary myelodysplastic syndromes. Issue 5 (May 1983) - Juneja, S K; Imbert, M; Sigaux, F; Jouault, H; Sultan, C
Abstract : In order to determine the prevalence and percentage distribution of ringed sideroblasts in primary myelodysplastic syndromes, the results of Prussian blue staining were analysed in 133 cases. Ringed sideroblasts ranging from 1 to 86% of cells were found in 76 (57%) cases. The cases of primary myelodysplastic syndrome corresponding to the group entitled "acquired idiopathic sideroblastic anaemia" had between 21 and 86% ringed sideroblasts; these were also found in 40% (26/65) cases corresponding to refractory anaemia with excess of blasts. Seven of the 22 cases having morphological features of refractory anaemia with excess of blasts in transformation had ringed sideroblasts. It would appear that cases of acquired idiopathic sideroblastic anaemia have at least 20% ringed sideroblasts; they also seem to occur frequently in refractory anaemia with excess of blasts.